Bahrain’s competitiveness as an international tourism destination among the Gulf Cooperation Council countries - Emmanuel, Melisa Mable (2009)
This study is an attempt to analyse the tourism potentials of the Middle Eastern state of Bahrain which is among those destinations that contribute to the rising popularity of tourism in the region which sets the need for competitive sustainability among them. The Kingdom’s competitiveness is analysed among fellow Gulf Cooperation Council states of Kuwait, Qatar, Oman, Saudi Arabia and the UAE. Thus the theoretical framework followed in the study and analysis is a model of competitiveness and sustainability. On analysing academic literature in light of the study, Bahrain’s tourism industry is analysed based on the secondary source of data collected in the research process. This data is then inculcated into the competitive backdrop of Bahrain as a tourism destination in comparison to the other GCC states. The review and analysis of data is then followed by discussion of findings for which recommendations have also been given so that Bahrain further develops into and sustains a competitive position in the GCC tourism market.